2018
DOI: 10.1016/j.enbuild.2018.04.006
|View full text |Cite
|
Sign up to set email alerts
|

In-situ real time measurements of thermal comfort and comparison with the adaptive comfort theory in Dutch residential dwellings

Abstract: a b s t r a c tIndoor thermal comfort is generally assessed using the PMV or the adaptive model. This research presents the results obtained by in-situ real time measurements of thermal comfort and thermal comfort perception in 17 residential dwellings in the Netherlands. The study demonstrates the new possibilities offered by relatively cheap, sensor-rich environments to collect data on clothing, heating, and activities related to thermal comfort, which can be used to improve and validate existing comfort mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…Table 4 summarizes the overview of the studies in Level 3 with different research domains. Nakama et al 2015, Riaz et al 2015, Tomasi et al 2015, Pasini et al 2016, Suprabhas and Dib 2017, Kang et al 2018, Sava et al 2018, Zhong et al 2018, Atazadeh et al 2019, Ignatov and Gade 2019, Rashid et al 2019, Zhao et al 2019 Indoor Thermal Comfort Chang et al 2018, Ioannou et al 2018, Pasini 2018 Space Management Fang et al 2016, Teizer et al 2017, Ferreira et al 2018, Gong et al 2018, Ha et al 2018, Asadi et al 2019, Mahmood et al 2020 Hazards…”
Section: Level 3: Integration Of Bim and Iot Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 4 summarizes the overview of the studies in Level 3 with different research domains. Nakama et al 2015, Riaz et al 2015, Tomasi et al 2015, Pasini et al 2016, Suprabhas and Dib 2017, Kang et al 2018, Sava et al 2018, Zhong et al 2018, Atazadeh et al 2019, Ignatov and Gade 2019, Rashid et al 2019, Zhao et al 2019 Indoor Thermal Comfort Chang et al 2018, Ioannou et al 2018, Pasini 2018 Space Management Fang et al 2016, Teizer et al 2017, Ferreira et al 2018, Gong et al 2018, Ha et al 2018, Asadi et al 2019, Mahmood et al 2020 Hazards…”
Section: Level 3: Integration Of Bim and Iot Techniquesmentioning
confidence: 99%
“…Chang et al (2018) developed a framework using Dynamo to transform real-time sensing data from Arduino Microcontroller to Autodesk Revit, to achieve colorful visualization of indoor temperature and humidity as well as thermal comfort in BIM models, similar to the platform developed by Pasini (2018). However, Ioannou et al (2018) evaluated the adaptive thermal comfort model by comparing the estimated thermal comfort values quantitatively and qualitatively using real-time indoor temperature, relative humidity, metabolic rate, and clothing, which indicated that the adaptive thermal comfort model would overestimate or underestimate the results.…”
Section: Indoor Thermal Comfortmentioning
confidence: 99%
“…Its instantaneous measured values differed from mean air temperature and mean floor temperature from −0.85 °C to 0.92 °C and from −3.90 °C to 2.48 °C, respectively. Regarding comments presented in [64,[90][91][92] operative temperature was calculated as average of air and radiant components [93,94].…”
Section: Thermal Comfort According To En Iso 7730mentioning
confidence: 99%
“…make part of factors' list that need to be taken in consideration. However, since all possible factors may vary in time and depend on different situations of workers, we decided to base our standard of occupants performance productivity, in this study, on the ASHRAE Standard 55, like in [2,3,8,9,10]. The ASHRAE determine a seven-point thermal scale (3= cold, -2 = cool, -1 = slightly cool, 0= neutral, 1= slightly warm, 2= warm, 3= hot).…”
Section: Use Casementioning
confidence: 99%